Maximizing strength development in athletes: A meta-analysis to determine the dose-response relationship - Peterson, M. D.; Rhea, M. R.; Alvar, B. A. (The Journal of Strength and Conditioning Research, 2004)
The efficiency, safety, and effectiveness of strength training programs are paramount for sport conditioning. Therefore, identifying optimal doses of the training variables allows for maximal gains in muscular strength to be elicited per unit of time and also for the reduction in risk of overtraining and/or overuse injuries. A quantified dose-response relationship for the continuum of training intensities, frequencies, and volumes has been identified for recreationally trained populations but has yet to be identified for competitive athletes. The purpose of this analysis was to identify this relationship in collegiate, professional, and elite athletes. A meta-analysis of 37 studies with a total of 370 effect sizes was performed to identify the dose-response relationship among competitive athletes. Criteria for study inclusion were (a) participants must have been competitive athletes at the collegiate or professional level, (b) the study must have employed a strength training intervention, and (c) the study must have included necessary data to calculate effect sizes. Effect size data demonstrate that maximal strength gains are elicited among athletes who train at a mean training intensity of 85% of 1 repetition maximum (1RM), 2 days per week, and with a mean training volume of 8 sets per muscle group. The current data exhibit different dose-response trends than previous meta-analytical investigations with trained and untrained nonathletes. These results demonstrate explicit dose-response trends for maximal strength gains in athletes and may be directly used in strength and conditioning venues to optimize training efficiency and effectiveness.